Pengaruh dan Kontribusi Organisasi Nahdlatul Ulama pada Masyarakat Juwangi - Dora Lathifa Nurwachida (Journal of Nahdlatul Ulama Studies, 2023)
Nahdlatul Ulama (NU) has contributed to Indonesian society through various aspects. As in its history, Nahdlatul Ulama has played a role in fighting Dutch colonization, seizing independence, and maintaining the sovereignty of the Indonesian state. In addition, Nahdlatul Ulama has also contributed to Islamic religious education, promoting the values of tolerance, harmony, and togetherness through educational, political, and interfaith channels. Not only that, but Nahdlatul Ulama also contributes to society. One of them is the Juwangi Boyolali community. In the Juwangi Village community, Nahdlatul Ulama has contributed quite a bit. Among them are contributions to social activities and religious activities. The Nahdlatul Ulama leaders in Juwangi Village also provide a touch of da'wah that makes the community comfortable, namely through the da'wah method of example. So these Nahdlatul Ulama leaders do not only lecture or preach. However, they also apply, so that what is preached by them can easily enter the hearts of the community, and eventually take root and become a positive habit for the community.Keywords: Nahdlatul Ulama, society, contribution, influence